Analiza wybranych uprawnień Europejskiego Urzędu Nadzoru Ubezpieczeń i Pracowniczych Programów Emerytalnych oraz ich wpływu na kompetencje Komisji Nadzoru Finansowego - Komarnicki, Grzegorz (Wydawnictwo Naukowe UAM, 2015)
This article presents an analysis of selected competencies of the European Insurance and Occupational Pensions Authority (EIOPA), namely the power to resolve disputes between national supervisory authorities i n the framework of a binding mediation and to issue non-binding guidelines, and the impact which exercising those powers by the EIOPA has on the competences of the Polish Financial Supervision Authority (KNF), a public authority responsible for the supervision of the Polish ﬁ nancial market.In the ﬁ rst part of the article the powers of the EIOPA to resolve disputes in a binding mediation process are described, and the limited possibilities that the EIOPA has to initiate this procedure are emphasized, since as a consequence of that the current mediation procedure encourages national supervisory authorities to resolve their disputes themselves. Next the principles of taking decisions by the EIOPA Board of Supervisors in the mediation process are described and attention is drawn to the discriminatory nature of those rules where the dispute relates to decisions of the group supervisor. The article also highlights potential consequences of decisions taken by the EIOPA within the binding mediation and their impact on administrative decisions taken by national supervisory authorities.The second part of the article provides an analysis of EIOPA’s powers to issue guidelines. The non-binding nature of the guidelines, which are described as soft law, has been reviewed. It is pointed that the European Union law provides for certain mechanisms which enable the EIOPA to enforce implementation of the guidelines by national competent authorities. As a next step, EIOPA guidelines on preparing for the implementation of Solvency II and the powers of the KNF to apply those guidelines have been reviewed. In addition to that, justiﬁ cation for vesting the KNF with the power to issue recommendations or guidelines addressed to insurance and reinsurance undertakings, in the context of analogous competences possessed by the EIOPA have been discussed.
Analysis of selected powers of the European Insurance and Occupational Pensions Authority and their impact on the competences of the Polish Financial Supervision Authority
Keywords: EIOPA; binding mediation; guidelines; Polish Financial Supervision Authority